PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN, RISK TOLERANCE, DAN EFIKASI KEUANGAN TERHADAP KEPUTUSAN BERINVESTASI - Juan Mandala Putra; Hendratmoko, Christiawan (Bajang Institute, 2024)
The aim of this study is to determine the effect of financial literacy, financial behavior, risk tolerance, and financial efficacy on investment decision. The population of this study are students who became investors in the Gallery of Investment in the college in Surakarta and 87 respondents are selected, using the stratified proportional random sampling technique. The data collection method uses a questionnaire method that is measured using a Likert Scale. To analyze the data using the data instrument test, the classical assumption test and multiple linear regression analysis. The results showed that financial literacy has a significant positive effect on investment decision and financial behavior has a significant positive effect on investment decision. While risk tolerance does not have a significant positive effect on investment decision and financial efficacy does not have a significant negative effect on investment decision. The advice in this research are the investment gallery to add socialization and education to the knowledge of financial behaviour and financial literacy to students, as well as for subsequent research to add other variables that do not exist in the this research.